Ultrastructural basis for interactions between central opioids and catecholamines. I. Rostral ventrolateral medulla - Milner, TA (J Neurosci, 1989)
Opioids and some alpha 2-adrenergic agonists are both known for their potent hypotensive actions following local application to the rostral ventrolateral medulla (RVL), in particular the region containing the C1 adrenergic neurons. We sought to determine whether coexistence and/or synaptic interactions might account for the commonality of cardiovascular responses to opioids and catecholamines in the RVL. Dual light and electron microscopic (EM) immunoperoxidase labeling of a rat monoclonal antibody against the opioid peptide Leucine5 (Leu5)- enkephalin and immunoautoradiographic localization of a rabbit antiserum against the catecholamine synthesizing enzyme tyrosine hydroxylase (TH) were examined in single sections through the RVL of adult colchicine-pretreated rats. Cross-reactivity of the enkephalin antibody was most intense with Leu5-enkephalin. Methionine5-enkephalin as well as dynorphin A, but not beta-endorphin, were also recognized by the antisera. By light microscopy, the Leu5-enkephalin-like immunoreactivity (LE-LI) was identified by peroxidase reaction product in perikarya and processes. Most of the perikarya containing LE-LI were located dorsolaterally or ventromedially to those showing immunoautoradiographic labeling for TH. However, a few perikarya appeared to contain both LE-LI and TH-immunoreactivity (TH-I) which were difficult to differentiate by light microscopy. By EM, perikarya and dendrites immunoreactive for LE, TH, and both LE and TH were readily distinguishable. Perikarya and dendrites immunoautoradiographically labeled for TH alone were more numerous than those containing LE-LI or TH-I and LE-LI. Axon terminals also were immunolabeled either for one or both reaction products. However, the TH- labeled neurons constituted one of the primary (42% from a total of 118) targets of terminals containing LE-LI. Additionally, some of these terminals containing LE-LI shared a common target with TH-labeled terminals. These common target neurons contained either TH-I or TH-I and LE-LI. In most cases, the identified junctions were symmetric and the terminals with LE-LI (0.4–1.2 microns in diameter) contained either (1) a few small clear vesicles (scv's) and numerous intensely immunoreactive large (100–150 nm) dense-core vesicles (dcv's); or (2) many scv's and from 0–6 dcv's of a somewhat smaller (80–120 nm) diameter. The latter type of terminal was more consistently dually labeled for TH. The remaining terminals containing LE-LI formed synaptic junctions with unlabeled perikarya or dendrites (32%), were in apposition to other unlabeled as well as TH or LE- and TH-containing terminals (4%) or were without recognizable specializations within the plane of section (22%).(ABSTRACT TRUNCATED AT 400 WORDS)